EFEKTIVITAS PERAN PEMERINTAH KOTA MAKASSAR DALAM PELESTARIAN CAGAR BUDAYA (TELAAH SIYASAH SYAR’IYYAH) - Hardianti, Sitti; Larissa, Dea; Hisbullah, Hisbullah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
Cultural heritage is the cultural heritage of the nation that should be preserved its existence. Makassar City Government has issued a policy as an effort to preserve cultural heritage as stated in Regional Regulation No. 2 of 2013 concerning Preservation of Cultural Heritage. The purpose of this study is to find out the effectiveness of the role of the Makassar City Government in preserving cultural heritage by using siyasah syar’iyyah analysis knives. This research is field research with data sources in the form of primary and secondary data. The results showed that the preservation of cultural heritage carried out by the Makassar City Government through the Makassar City Cultural Office was quite effective by looking at several indicators of performance effectiveness in Islam known as al-Fauz. The effectiveness of the role of the government is one of the elements of the principle of good governance or good governance that is in line with the principles of siyasah syar’iyyah.